The Tell ’Uqair temple (4th mill.BC) : colours and iconography - Dermech, Sarah (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
Date: ca. 3400-3100 BC, late Uruk period, first urbanization of south Mesopotamia. Location: Tell ‘Uqair, Babylonia, Iraq. Abstract: This contribution presents the “painted temple” of Tell ‘Uqair, which has provided evidences for bright paintings on the interior. Based on the archaeological report, as well as on in-depth comparisons with other urukean building, we focus on a colorful reconstruction of one of the characters, offering new interpretation of its symbolic meaning.